Algal uptake of hydrophilic and hydrophobic dissolved organic nitrogen in the eutrophic lakes. (January 2019) - Feng, Weiying; Liu, Shasha; Li, Cuicui; Li, Xiaofeng; Song, Fanhao; Wang, Beibei; Chen, Haiyan; Wu, Fengchang
Abstract: Dissolved organic nitrogen (DON) derived from sediments plays an active role in biogeochemical cycling of nutrients in aquatic ecosystems. Sediments from four eutrophic lakes were studied using three-dimensional fluorescence excitation-emission matrix (3DEEM) spectra and supelite XAD-8 macroporous resin separation to investigate the bioavailability of hydrophilic and hydrophobic DON to algae ( Microcystis flos-aquae (Wittr.) Kirchner). The results showed that the average loss of DON was <6.0% after dividing DON into hydrophilic and hydrophobic components, demonstrating the utility of XAD-8 resin separation in the study of DON components from lake sediments. The 3DEEM analysis showed that hydrophobic and hydrophilic DON comprised humic- and protein-like materials, respectively. During the incubation period, the bioavailability of hydrophilic DON, which accounted for 59.3%–80.4% of total DON, stimulated algal growth, suggesting that hydrophilic DON was the primary source of organic nitrogen for algae. In contrast, hydrophobic DON increased algal density by only 31.8% of that observed for hydrophilic DON, and had a small (accounted for 20.0%–26.6% of total DON) effect on algal growth over the short-term. The significant differences in algal growth between the two types of DON suggested that they should be considered separately in the eutrophic lake restorations. Graphical abstract: Image 1 Highlights: DON from lake sediments was divided into hydrophilic and hydrophobic components using XAD-8 resin separation technique. Bioavailability of hydrophobic and hydrophilic components were investigated by 3DEEM spectra. Hydrophilic of DON was the primary source of algae growth in the eutrophic lakes. The differences between the two types of DON will be useful in better understanding nitrogen cycling for eutrophic lakes.